Application of Local Wisdom Values in Sales Accounting Practices in Traditional Markets - Mildayanti; Antong; Halim Usman (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
This study aims to determine the concept of determining the selling price in traditional markets from the perspective of vegetable traders. The method in this study uses a qualitative method with a phenomenological approach. Phenomenology tells according to what exists and occurs in the object of research. The source of research data comes from the results of observations, interviews, and documentation with traders in traditional markets. On the other hand, the main purpose of using phenomenology to find the concept of the selling price in this study is to focus on finding the nature behind the attitudes and behavior of information providers in setting prices. Several vegetable traders served as information providers for this study. The results found that traders determine the selling price by using two sales methods, namely the weighing method and the tekem method or hand measurement method. In determining profit, traders calculate the profit per kilogram of vegetables. Starting with Rp. 1,000/kg to Rp. 2,000/kg with the weighing method. As for vegetables with the tekem method, it ranges from Rp. 500/bunch to Rp. 1,000/bunch. In traditional markets, buyers and sellers carry out negotiation or bargaining activities, unlike modern markets that have determined the selling price of their merchandise. Keywords: accounting practices, traditional traders, selling price, bargaining.